Innovative use of mine tailings as a soil amendment for growing Pisum sativum L. - Mohammed Kharbouche; Khalid El Khalidi; Redouane Mghaiouini; Ahmed Aajjane; Bendahhou Zourarah (Plant, Soil and Environment, 2025)
This study investigates the benefits of using mine tailings (MT) to improve pea (Pisum sativum L.) growth and productivity on degraded agricultural soils in semi-arid environments. The research aims to evaluate the use of MT as an innovative soil amendment and to determine the optimal dose required to enhance the micronutrient availability of Zn, Mn, Cu and Fe without affecting soil quality. The experiment was conducted in greenhouse pots with three different soil types amended with different MT doses (control and four doses). Soil samples were collected from the Doukkala region, one of the main agricultural areas in Morocco. Pea was grown in pots and monitored for 87 days until maturity. After harvest, soil and plant samples were weighed, measured and analysed by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The experiment found that moderate doses (0.2 g/kg to 1 g/kg) applied to all soil types promoted optimal pea growth by improving plant height, root and above-ground biomass and pod number. Thus, MT can act as a biostimulant. However, nutrient antagonism negatively affected growth at the highest dose (4 g/kg). Bioconcentration and translocation factors indicated efficient micronutrient uptake and biofortification, while heavy metals remained immobilised in roots, effectively eliminating toxicity risks.